6. SATISFACTION OF HEALTH WORKERS WITH THE QUALITY OF POLICIES AT DISTRICT HOSPITALS, THANH HOA PROVINCE, 2020-2021 (Vietnam Journal of Community Medicine, 2022)
Background: The satisfaction survey of health workers helps the hospital’s Board of Directorsunderstand their thoughts and aspirations, thereby building and adjusting the appropriate qualitypolicies and building their loyalty and enthusiasm for the hospital.Objectives: Describe the satisfaction of health workers with the quality of medical examination andtreatment services at district hospitals.Methods: Cross-sectional survey, quantitative research.Results: This study collected information from 300 health workers in six districts of the hospital inThanh Hoa province through questionnaires. The results showed that health workers’ quality andsatisfaction rates were relatively high, with scores and rates respectively (3.63 - 4.18 points) and(73% - 83.6%).
Keywords: Satisfaction, Quality of policies, Health workers.